IMPLEMENTASI APLIKASI PENGELOLAAN GUDANG WAREHOUSE MENGGUNAKAN QR KODE BERBASIS ANDROID - Febry harlian hasibuan; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2023)
PT. Simatelex is engaged in the industry of household electrical appliances and electric heaters. This company has several lots or buildings that are used as warehouses A, B, C, D. In sending goods from one building to another, they still use manual methods, so there are buildings that experience overstock of goods due to invalid data. The number of goods requested at the store by production is often excessive or lacking. Goods in each building are often overstocked and data reports sent to superiors often experience delays. The purpose of this study is to design and implement a warehouse warehouse management application using an Android-based Qr Code. By using Android Studio software and MySQL database. The program can be used for Android version 10. These results can be useful to help employees, especially the store section, to make their work easier. In designing a warehouse warehouse management application using a display design that is easy for users to understand and by using barcode scans, users will easily get appropriate information and do not need to spend a lot of time finding the goods needed.